O sentido de ser educadora das/nas brinquedotecas do Hospital Infantil de Vitória/ES : um estudo a partir dos conceitos de experiência, narrativa & cuidado - Bragio, Jaqueline (2014)
The act of play has been regarded as vital to mental health, emotional, physical and intellectual human being. All these elements are experienced in the play independent mode. The Hospital playroom provides better conditions for the recovery of the child in the facility, minimizing trauma and situations making their hospital stay more joyful. This dissertation proposes a study of phenomenological existential inspiration AIMING: unveiling-the sense of being an educator in the playrooms of the Children's Hospital of Vitória/ ES, focusing on the experiences of them narrated and thoroughly experienced (or experienced) subjective modes of them be in the objective world, experiences which will be narrated by them in this space- time of playfulness that lends itself to Hospital Pedagogy in their strands of school attendance (special education in an inclusive perspective) and outside school settings where hospital pedagogy composes a branch of Social pedagogy, thus offering care to children and young people especially, but not only (which may include adults and seniors). THEORETICAL PERSPECTIVE: the central theoretical term of our theoretical perspective is Care (SORGE), as in BOFF (2012) and WALDOW (1993; 1998; 2006) and Experience in PINEL (2004; 2006) to be (have been) somehow creator of this space-time playing (and study) at the hospital, consulting both a No School Education (Social Pedagogy) and School (School Pedagogy).The anguish of being an educator of playrooms it seemed to us that you will be in a feature essential to understanding their existence of being in the craft, as well as their interaction with oneself, with others and with the world of Hospital Playrooms. We understand the meanings of happiness, calm and happiness, courage and professionalism, transform (action), law and education and humanization and pain as elements that composed the complex mosaic of Care (Sorge) – own that it proposes to take care of themselves, each other and the things of the world by the bias of caring.